The cross and the switchblade - Wilkerson, David, 1931-2011.; Sherrill, John L.; Sherrill, Elizabeth (New York : Jove Books, 1977)
A minister who left his small town church to go to New York City relates his experiences working with street gang members.
"A Jove/HBJ book."
Keywords: Church work with juvenile delinquents -- United States; Wilkerson, David, -- 1931-2011.